A Possible Association between Deep Molecular Response and Combination of Tyrosine Kinase Inhibitor and Immunochemotherapy in a Patient with Coexisting Chronic Myeloid Leukemia and Follicular Lymphoma: A Case Report - Wen-Yung Tsai; Cih-En Huang (Journal of Cancer Research and Practice)
Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of chronic myeloid leukemia (CML) and improved survival rates, however, concerns about TKI-related secondary malignancies persist. We report the case of a 55-year-old male with chronic phase CML who achieved a minimal molecular response (MR3.0) under nilotinib treatment. The patient subsequently developed multiple lymphadenopathies and was diagnosed with follicular lymphoma. After receiving bendamustine and rituximab (BR) with rituximab maintenance therapy, he not only achieved complete remission of follicular lymphoma but also an unexpected improvement in CML molecular response from MR3.0 to MR4.5. This case highlights both the potential risk of TKI-related secondary malignancies and the unexpected improvement in molecular response following immunochemotherapy. The improved molecular response after BR therapy suggests possible synergistic effects between TKIs and immunochemotherapy. Although the definite mechanism remains unknown, immunomodulatory mechanisms similar to those observed with interferon-alpha in CML treatment may be a potential explanation. Further investigations into the role of immunochemotherapy in achieving a deeper molecular response in CML patients are warranted.